An investigation on mode II fracture toughness enhancement of epoxy adhesive using graphene nanoplatelets. (15th December 2018) - Jia, Zhemin; Feng, Xiaoping; Zou, Yun
Abstract: Epoxy adhesive has a great potential use in different areas which may encounter impact loadings, the fracture behavior of epoxy adhesive needs to be improved to meet the safety requirement. This paper experimentally studies the dynamic mode II fracture toughness of an epoxy adhesive reinforced by different content of graphene nanoplatelets (GNPs) through compliance-based beam method (CBBM). Typical R-curves of the neat epoxy adhesive and nanocomposites with different graphene content under the loading rate of 2  m/s are obtained. From the experimental results, the dynamic critical strain energy release rate of nanocomposites increases compared with the value of neat epoxy indicating the effectiveness of graphene on dynamic mode II fracture toughness improvement. The dynamic mode II fracture toughness of nanocomposites reinforced by 0.5 wt% GNP exhibits a 41% enhancement compared with neat epoxy adhesive, while no further increase is observed when the nanocomposites loaded with the GNP content of 0.75 wt%.